The effects of working capital management on the profitability of Nigerian manufacturing firms - Aregbeyen, Omo (Journal of Business Economics and Management, 2013)
The efficiency of working capital management (WCM) has implications for firms’profitability. This paper empirically investigates the effects of WCM on the profitability of a sample of 48 large manufacturing firms quoted on the Nigerian Stock Exchange (NSE) for the period 1993 to 2005. It is aimed at filling the gaps in a previous study and contribute to expanding and enriching the literature particularly on Nigeria and at large. The analysis examined the responses of the firms’ profitability to WCM and a number of augmenting factors. Profitability was alternatively measured by gross operating profit (GOI), net operating income (NOI) and return on assets (ROA). Likewise, WCM was measured by the average collection period (ACP), average pay period (APP), inventory turnover days (ITID) and comprehensively by the cash conversion cycle (CCC). The results indicate that the firms’ have been inefficient with WCM and caused significant reductions in profitability. The paper concludes that improving the efficiency of WCM is essential and recommends that manufacturing firms in Nigeria should shorten the ACP, APP, ITID and reduce their CCCs.